ENVIRONMENTAL MEDIA ACTIVISM JOURNALISM: contributions from an analysis of journalistic coverage of the Amazonia Real - Miguel, Katarini Giroldo (2023)
Our research aims to understand and problematize the proximity between environmental journalism and media activist practice based on the Journalistic Coverage Analysis (SILVA, MAIA) of the Amazônia Real portal, adapted to our empirical efforts in a media activist environmental journalism protocol. We present, in this article, the methodological steps of two reports that highlight the strength of the assumptions of environmental journalism: emphasis on contextualization, plurality of voices, assimilation of environmental knowledge (Loose and Girardi, 2017); the discursive tactics of mediativism, but also the underuse of resources and the way events are presented. More than reported, they should be protested, within the scope of the manifesto-report.